402 Psychological response to injury in collegiate male and female gaelic games players. (3rd March 2020) - O'Connor, Siobhán; Sheridan, Aishling; Brady, Shaunagh; Bruce, Conor; Whyte, Enda
Abstract : Background: Gaelic games are popular male and female collegiate sports. Injuries are common in collegiate Gaelic games, with physical and psychological consequences. Behaviours such as fear-avoidance and lowered confidence can occur post-injury and may have a detrimental impact on a player's recovery and return to sport. Objective: This study aimed to examine the psychological response to injury in male and female collegiate Gaelic games players. Design: Prospective cohort study Setting: Collegiate athletics in one Irish institution Patients (or Participants): Male (n=150) and female (n=76) collegiate Gaelic games players. Interventions (or assessment of risk factors): All players that sustained an injury over one collegiate season completed two validated questionnaires: the Athlete Fear Avoidance Questionnaire (AFAQ) immediately following injury and the Injury-Psychological Readiness to Return to Sport (I-PRSS) once cleared to return to play. Student athletic therapists and trainers, present at all trainings and games, examined any injuries and referred them to a Certified Athletic Therapist. Main outcome measurements: The total AFAQ (sum of 10 items) and I-PRSS (sum of 6 items divided by 10) scores were calculated. An independent samples t-test examined gender differences in both scales and a one-way ANOVA determined differences between injury severity (mild/moderate/severe). Descriptive statistics were also measured. Results: Seventy-three injuries were recorded with AFAQ and I-PRSS scores of 22.5±5.3 and 46.4±8.8 noted. No gender differences were observed (p>0.05). The lowest scores were observed in 'I will never be able to play as I did before my injury' and 'My confidence to not concentrate on the injury is..' variables. Higher fear avoidance (p=0.009) and lower confidence levels (p=0.04) were noted in those with severe injuries. Conclusions: Fear-avoidance and low confidence levels was noted in this population, particularly following severe injuries. These scales can identify those at risk and facilitate addressing these issues during rehabilitation to ensure players are psychologically ready to return to play.